Analisis Konsumsi Pangan Hewani pada Tingkat Rumah Tangga di Daerah Istimewa Yogyakarta - Irene Eka Wijayanti; Masyhuri Masyhuri; Ken Suratiyah (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 1999)
The objectives of the study are to recognize the factors influence animal food consumption (catfish, beef, chicken, chickens egg, condensed sugar milk), income elasticity value of animal food consumption, own price elasticity value of animal food consumption, and amount of animal protein consumption by the people in special region Yogyakarta Province.